(untitled) (PANGEEA, 2026)
The article proposes the use of facilities offered by the Google Earth Engine platform for the study and analysis of problems and documentation of decisions in the field of water resources management. The features of the Google Earth Engine (GEE) platform are presented, including the input of data sources, and their use is exemplified by implementing automated procedures using the JavaScript language. Available geospatial data are processed for the purpose of identifying and monitoring water bodies using the Automated Water Extraction Index (AWEI).